The Role of Anti-Fraud Policies in Moderating the Influence of the Fraud Hexagon on Financial Statement Fraud at Islamic Commercial Banks in Indonesia - Septi Hasna Rizki; Slamet Wahyudi; Luqman Hakim (Publikasi Indonesia, 2025)
Based on SFAC (Statement of Financial Accounting Concepts) No. 8, the purpose of financial reporting is to provide relevant financial information to external users to support their decision-making. This study aims to examine the influence of pressure, capability, collusion, opportunity, rationalization, and ego on financial statement fraud at Islamic Commercial Banks in Indonesia by considering the role of anti-fraud policies as a moderating variable. This study employs a quantitative approach using panel data from eight Islamic Commercial Banks over the period 2018–2024, analyzed using fixed-effects regression. The results indicate that anti-fraud policies are unable to moderate the influence of pressure and capability on financial statement fraud. However, anti-fraud policies effectively moderate the influence of collusion, opportunity, rationalization, and ego, thereby reducing or weakening financial statement fraud. These findings reinforce the validity of fraud theory in the context of Islamic Commercial Banks and emphasize the importance of implementing effective anti-fraud policies to mitigate behavioral and systemic fraud risks. The practical implications of this study highlight the need to strengthen internal oversight and organizational ethical culture as part of a sustainable fraud prevention strategy in the Islamic commercial banking sector.